Pengaruh Personal Space Terhadap Kenyamanan Belajar Ruang Studio Gambar Arsitektur Universitas Hasanuddin - Kahir, Shapardi; Yusriadi, Yusriadi (Nature: National Academic Journal of Architecture, 2024)
The drawing studio is a space where students complete core architectural design courses in the architecture department. The studio is a space for carrying out various activities such as discussions with fellow participants and lecturers, making programs and plans, conducting precedent studies, presenting images, looking for ideas, and making designs. This research aims to identify students’ personal space in the drawing studio room of the architecture department at Hasanuddin University and its influence on study concentration. This research uses a qualitative descriptive method. A purposive sampling strategy was used to collect data through questionnaires and interviews. Descriptive analysis method to analyze data regarding students’ personal space in learning. There were 64 people in the research sample, namely 30 people from the 2019 class and 34 people from the 2018 class. The research results show that students’ personal space is divided into 4 distance groups: intimate distance, personal distance, social distance, and public distance. Situational factors, individual activities, personality, gender, and age are things that influence personal space. Personal space has an influence on concentration in studying in the drawing studio room. The close proxemic distance makes it more difficult for students to carry out activities so concentration decreases, while the longer proxemic distance makes students more free to carry out activities and can concentrate better. Distance between individuals is one of the variables that influences learning comfort.